The non-thermal emission from the colliding-wind binary Apep. (31st January 2022) - del Palacio, S.; Benaglia, P.; De Becker, M.; Bosch-Ramon, V.; Romero, G. E.
Abstract: Therecently discovered massive binary system Apep is the most powerful synchrotron emitter among the known Galactic colliding-wind binaries. This makes this particular system of great interest to investigate stellar winds and the non-thermal processes associated with their shocks. This source was detected at various radio bands, and in addition the wind-collision region was resolved by means of very-long baseline interferometric observations. We use a non-thermal emission model for colliding-wind binaries to derive physical properties of this system. The observed morphology in the resolved maps allows us to estimate the system projection angle on the sky to be $ψ ≈ 85^°$ . The observed radio flux densities also allow us to characterise both the intrinsic synchrotron spectrum of the source and its modifications due to free–free absorption in the stellar winds at low frequencies; from this, we derive mass–loss rates of the stars of $\dot{M}_WN ≈ 4×10^{-5}\;M_\odot\, yr^{-1}$ and $\dot{M}_WC ≈ 2.9×10^{-5}\;M_\odot\, yr^{-1}$ . Finally, the broadband spectral energy distribution is calculated for different combinations of the remaining free parameters, namely the intensity of the magnetic field and the injected power in non-thermal particles. We show that the degeneracy of these two parameters can be solved with observations in the high-energy domain, most likely in the hard X-rays but also possibly in $γ$ -rays under favourable conditions.